Engineering analysis of the dynamic characteristics of an electrical jacket platform of an offshore wind farm under seismic loads. (July 2021) - Zhao, Sheng-Xiao; Bi, Chun-Wei; Sun, Zhen-Zhou
Highlights: A finite element model is established and validated by the corresponding model test. Dynamic response of a jacket offshore electrical platform under earthquake is studied. Dynamic amplification factor of the top-heavy structure under earthquake is discussed. Abstract: From the perspective of the power transmission economy, offshore electrical platforms will be an inevitable choice for developing large-scale offshore wind farms in the open sea. In this study, a finite element numerical model of the electrical platform was built, and the dynamic responses under seismic loads were analyzed. The validity of the numerical model was verified by the corresponding physical model test. On this basis, a time-history analysis of the strain, acceleration, and displacement response of the electrical platform was carried out. The results and trends of dynamic responses under different wave actions were obtained. The influence of water and air environments and unidirectional and bidirectional seismic excitations on the dynamic response of the structure was analyzed. Consequently, the strain peaks of the structures under air conditions are all greater than those under water conditions, with an increment mean of 12.88%, and an increment mean of the peak acceleration of 10.76%. The peak value of the acceleration response is 30.49% higher than that of the unidirectional earthquake, and the peak value of the strain response is 25.78% higher than that of the unidirectional earthquake. It is indicated that bidirectional seismic excitation is more detrimental to the safety of structures.